Correlation of Serum Zinc with Blood Pressure in Hypertensive Individuals - SMR, Rahman; AK, Pramanik; K, Fatema; AKMS, Rahman; S, Sultana; MS, Yesmin; MMA, Bhuiyan; MT, Islam; MS, Islam; T, Sultana (Archives of Clinical and Biomedical Research, 2021)
Background: Hypertension is one of the leading causes of mortality and morbidity worldwide. Trace elements deficiencies are believed to be related with development of hypertension and associated complications. Objective: To explore the correlation of serum zinc with blood pressure in hypertensive individuals. Methods: This study was conducted at the Department of Laboratory Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from March 2020 to February 2021. A total of 100 adult subjects were selected purposively, among them 50 were diagnosed cases of hypertension and 50 were normotensive healthy adults as control group. Their blood pressure (BP) was measured and body mass index (BMI) was calculated accordingly. Serum zinc and serum lipid profile [Total Cholesterol (TC), High Density Lipoprotein- Cholesterol (HDL-C), Low Density Lipoprotein- Cholesterol (LDL-C) and Triglyceride (TG)] of the study subjects were measured. Data were analyzed and compared by statistical tests. Results: The mean(±SD) age was 46.9±12.7 years in hypertensive patients and 43.1±8.5 years in control group. Male subjects were predominant in both groups. Majority of the hypertensive patients were found over-weight. Mean(±SD) levels of serum TC, LDL-C, TG were significantly high (p<0.05) and mean serum HDL-C level was significantly low (p=0.018) in hypertensive group. Mean(±SD) serum zinc level was significantly low (p=0.020) in hypertensive group. In hypertensive group, serum zinc had significant negative correlation with systolic blood pressure [SBP (r= - 0.620, p<0.001)] and diastolic blood pressure [DBP (r= - 0.446, p=0.001)]. Conclusion: The serum zinc level is significantly low in hypertensive individuals. Serum zinc has a negative correlation with systolic and diastolic blood pressures in hypertensive individuals.